Effects of ?-3 essential fatty acids against formaldehyde-induced nephropathy in rats - Zararsiz, Ismail; Sonmez, Mehmet Fatih; Yilmaz, H. Ramazan; Tas, Ufuk; Kus, Ilter; Kavakli, Ahmet; Sarsilmaz, Mustafa (Sage Publications Inc, 2006)
The aim of this study was to examine the toxicity of formaldehyde ( FA) on the kidney and the protective effects of omega-3 essential fatty acids against these toxic effects. Twenty-one male Wistar rats were divided into three groups. Rats in Group I comprised the controls, while the rats in Group II were injected every other day with FA. Rats in Group III received omega-3 fatty acids daily while exposed to FA. At the end of the 14-day experimental period, all rats were killed by decapitation and the kidneys removed. Some of the kidney tissue specimens were used for determination of superoxide dismutase ( SOD), glutathione peroxidase (GSH-Px) activities, and malondialdehyde (MDA) levels. The remaining kidney tissue specimens were used for light microscopic evaluation. The levels of SOD and GSH-Px were significantly decreased, and MDA levels were significantly increased in rats treated with FA compared with those of the controls. Furthermore, in the microscopic examination of this group, glomerular and tubular degeneration, vascular congestion and tubular dilatation were observed. However, increased SOD and GSH-Px enzyme activities, and decreased MDA levels were detected in the rats administered omega-3 fatty acids while exposed to FA. Additionally, kidney damage caused by FA was decreased and structural appearance was similar to that of the control rats in this group. In conclusion, it was determined that FA-induced kidney damage was prevented by administration of omega-3 essential fatty acids.
Keywords: formaldehyde; kidney; rat; omega-3 fatty acids